The chemical synthesis, stability, and activity of MAIT cell prodrug agonists that access MR1 in recycling endosomes - Lange, J; Anderson, R; Marshall, A; Chan, S; Bilbrough, T; Gasser, O; Gonzalez-Lopez, C; Salio, M; Cerundolo, V; Hermans, I; Painter, G (American Chemical Society, 2020)
Mucosal-associated invariant T (MAIT) cells are antibacterial effector T cells that react to pyrimidines derived from bacterial riboflavin synthesis presented by the monomorphic molecule MR1. A major challenge in MAIT cell research is that the commonly used MAIT agonist precursor, 5-amino-6-d-ribitylaminouracil (5-A-RU), is labile to autoxidation, resulting in a loss of biological activity. Here, we characterize two independent autoxidation processes by LCMS. To overcome the marked instability, we report the synthesis of a 5-A-RU prodrug generated by modification of the 5-amino group with a cleavable valine-citrulline-p-aminobenzyl carbamate. The compound is stable in prodrug form, with the parent amine (i.e., 5-A-RU) released only after enzymatic cleavage. Analysis of the prodrug in vitro and in vivo showed an enhanced MAIT cell activation profile compared to 5-A-RU, which was associated with preferential loading within recycling endosomes, a route used by some natural agonists. This prodrug design therefore overcomes the difficulties associated with 5-A-RU in biological studies and provides an opportunity to explore different presentation pathways.